2019
DOI: 10.3390/jcm8040472
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic Efficacy of Dexmedetomidine versus Midazolam When Combined with Remifentanil for Percutaneous Transluminal Angioplasty in Patients with Peripheral Artery Disease

Abstract: Anesthesia for percutaneous transluminal angioplasty (PTA) involves a high-risk population having a broad spectrum of pain character and intensity. This study delved the anesthetic efficacy of dexmedetomidine versus midazolam, when used with remifentanil. Seventy patients scheduled for femoropopliteal PTA were randomized into two groups receiving either intermittent midazolam boluses (0.03–0.05 mg/kg) (MR group) or dexmedetomidine 0.2–0.7 μg/kg/h after a loading dose of 1.0 μg/kg for 10 min (DR group), both wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Of particular relevance to spinal anesthesia, both intrathecal and intravenous administration of dexmedetomidine extend the duration of sensory and motor blockades, deepen sedation, delay the time required for postoperative rescue analgesics, and reduce consumption of morphine during the postoperative 24 hours 18 , 23 . Indeed, cumulating evidence shows that dexmedetomidine is superior in terms of satisfaction for both patient and interventionists compared with midazolam 16 , 24 - 26 . In addition, patients sedated with dexmedetomidine exhibited lower pain values and lower analgesic requirements postoperatively 26 , 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular relevance to spinal anesthesia, both intrathecal and intravenous administration of dexmedetomidine extend the duration of sensory and motor blockades, deepen sedation, delay the time required for postoperative rescue analgesics, and reduce consumption of morphine during the postoperative 24 hours 18 , 23 . Indeed, cumulating evidence shows that dexmedetomidine is superior in terms of satisfaction for both patient and interventionists compared with midazolam 16 , 24 - 26 . In addition, patients sedated with dexmedetomidine exhibited lower pain values and lower analgesic requirements postoperatively 26 , 27 .…”
Section: Discussionmentioning
confidence: 99%
“…After confirmation of appropriate block height, dexmedetomidine infusion was initiated based on previous studies [16]. In both groups, dexmedetomidine 1.0 μg/kg was administered for 10 minutes followed by continuous infusion of 0.2-0.7 μg/kg/h until the end of surgery.…”
Section: Anesthetic and Procedural Managementmentioning
confidence: 99%
“…Park et al. 27 found that dexmedetomidine (0.2–0.7 μg/kg/hours) combined with remifentanil could reduce postoperative pain. Yu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, dexmedetomidine is adopted to relieve pain by combination with other agonists. Park et al 27 found that dexmedetomidine (0.2-0.7 lg/kg/hours) combined with remifentanil could reduce postoperative pain. Yu et al 9 suggested that dexmedetomidine 0.05 lg/kg/hour is a better choice for antishivering, which is consistent with our study.…”
Section: Discussionmentioning
confidence: 99%
“…Combination of opioids such as remifentanil with benzodiazepines or propofol may improve sedation experience, however, it can increase a risk of respiratory depression 65). Addition of dexmedetomidine can confer both sedation and analgesia while sparing the dose of opioids and preserving the respiratory function 66)…”
Section: Considerations For Specific Proceduresmentioning
confidence: 99%